Resilience to Climate Change Communication, Collaboration and Co-production - Howarth, Candice (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
'The challenge of coping with uncertain climate risks and potential disruption across a range of sectors is a topic that is increasingly coming to the fore... Dr. Howarth and colleagues skilfully set out the nature of the problem, the barriers to responding effectively, and some innovative thinking about the importance of collaboration and communication to improve resilience.' -Kristen Guida, London Climate Change Partnership, UK 'Anyone concerned with communication of environmental risks, public understanding of science and risk, and planning for resilient responses to environmental shocks to our systems, will benefit from reading this book and applying its lessons.' -Dr Ian Christie, University of Surrey, UK The frequency and intensity of climate shocks such as heatwaves and flooding, are expected to increase under a changing climate with severe implications across the food, energy, water, environment nexus. This book critically explores how to improve resilience to climate shocks by examining the range of challenges and opportunities that exist in the aftermath of shocks and discusses factors that exacerbate and mitigate these. It innovatively discusses the importance of embedding communication, collaboration and co-production within resilience-building across sectors and stakeholders. Doing so with policy, practitioner and scientific communities, Candice Howarth argues, can pave the way to overcome challenges that emerge from climate shocks and facilitate the co-design of sustainable, robust and resilient responses.